Analysis of Factors Affecting the Quality of Financial Statements at Regional Apparatus Organizations in Mataram City - Putri, Angguni Aminarti; Inapty, Biana Adha; Kartikasari, Nungki (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to identify the factors that influence the reliability of financial reports prepared by local governments in terms of human resource competency, internal control system, organisational commitment, and internal audit. A total of 138 participants filled out and returned the surveys used in this quantitative study, which used a purposive sampling methodology to choose its sample. The maximum number of surveys that could be processed was 100. Staff members from 36 different regional apparatus organisations in Mataram City who were employed in the finance department were the subjects of this study. Data analysis was conducted using SmartPLS4 software and the Partial Least Structural Equation Model (PLS-SEM). Humanz resource competency and internal audit both contribute to better financial statement quality, according to this study's findings.